Bolster Barrier (BOLER): A New Design to Improve Safety of Accidents - Salleh, Bibie Sara; Adamulhasza, Iskandar Zulkarnain; Samat, Nur'Izzah Sahirah; Amiruddin, Nur Qasrina; Haziq, Awangku Nazrul (International Journal of Sustainable Construction Engineering and Technology, 2017)
Guardrails are the most important road furniture as they prevent vehicles from crashing into the shoulder of the road or into the opposite lane. They also protect the objects at the roadside and prevent vehicles from entering into dangerous areas such a ravine or river. Performance of guardrails is not only influenced by their own design, but also the design of the vehicle. The design of guardrails is mostly aimed to reduce serious effects towards vehicles and users in an event of an accident. Bolster Barrier (BOLER) is an impact device that enhances the existing W-shape guardrails that are intended to reduce the accident impact between road users and the guardrails themselves. The application of BOLER is focused at critical areas. The purpose of this device is to reduce the numbers of serious injuries and fatalities in an accident. BOLER was put through an impact test known as dolly test at MIROS Lab, Provisional Crase Crash Centre (PC3), Ayer Molek, Melaka. The impact test that was carried out measured the dolly’s velocity, w-beam guardrail bar’s deformation and the overall force over time trace. Based on the results, both Standard w-beam guardrail alone and Standard w-beam with BOLER showed a different performance upon impact. Standard W-beam guardrail with BOLER recorded a lower peak force (47.6kN versus 51.5kN) and a delayed time to reach peak force by 11.4 milliseconds. The delay of 11.4 milliseconds creates a safe zone for an airbag to fully inflate before the full impact between road users and the guardrails occurs.